Structural and Optical Properties of CdS:20%In Films Prepared by Thermal Co-Evaporation method - Mona M. Saleh (مجلة بغداد للعلوم, 2010)
The CdS;In films of Thickness 7500Ao at( 20% In) concentration  have been Prepared by double evaporation method in Vacuum on glass substrate at 100co .